Czech Republic : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2010)
This 2010 Article IV Consultation discusses Czech Republic's economic condition. The Czech economy's fundamentals were strong prior to the global economic and financial crisis. However, owing to its highly open nature, the economy was hit by spillover effects. A downturn in the euro area depressed exports while investment declined owing to a drop in FDI and the tightening of banks' lending standards. Monetary and fiscal easing provided helpful stimulus, thereby cushioning the economic downturn.